Monitoring the financial assistance received by the critical infrastructure employees affected by the military aggression (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article reveals the results of the monitoring conducted by the Ukrainian Parliament Commissioner for Human Rights regarding the observance of the right to receive financial assistance by employees of critical infrastructure facilities, civil servants and local self-government officials affected by military aggression. The relevance of the topic is due to the fact that ensuring observance of the constitutional rights of citizens, and in the context of martial law, ensuring guarantees for employees whose activities are directly related to the victory over the aggressor is a priority for the State. The purpose of the article is to analyse the legislation regulating the issue of receiving a one-time financial benefit for damage to life and health caused to employees.The achievement of the above goal was made possible through the use of a set of methods of scientific knowledge, namely, dialectical, comparative legal, formal and logical, and systemic and structural methods. Based on the analysis, the research proves that the methodology for determining the critical infrastructure object does not meet the conditions of martial law. The author establishes the need to revise the sectoral and intersectoral criteria for determining the level of negative impact in the event of destruction (damage) of a critical infrastructure facility. The article emphasises the untimely adoption of bylaws and regulations, which results in a violation of the victims’ right to receive one-time assistance. The subjective factors of submitting inaccurate data for inclusion of an object in the Register of Critical Infrastructure Objects, which leads to a violation of this right, are emphasised. It is established that the Law of Ukraine “On Critical Infrastructure” does not comply with the provisions of Directive (EU) 2022/2557. On the basis of the study, the conclusions on the gaps in the legislation that lead to violations of the rights of this category of citizens are formulated.
Keywords: Ukrainian Parliament Commissioner for Human Rights; workplace injuries; critical infrastructure workers; financial assistance; compensation for health damage; martial law; military aggression.